Funding liquidity risk: definition and measurement - Mathias Drehmann; Kleopatra Nikolaou (European Central Bank (ECB), 2009)
In this paper we propose definitions of funding liquidity and funding liquidity risk and present a simple, yet intuitive, measure of funding liquidity risk based on data from open market operations. Our empirical analysis uses a unique data set of 135 main refinancing operation auctions conducted at the ECB between June 2005 and December 2007. We find that our proxies for funding liquidity risk are typically stable and low, with occasional spikes, especially during the recent turmoil. We are also able to document downward spirals between funding liquidity risk and market liquidity.
Keywords: E58; G21; 330; bidding data; funding liquidity; Interbank markets; liquidity risk; money market auctions; Geldmarkt; Zentralbank; Auktion; Bankenliquidität; Risiko; Marktliquidität; EU-Staaten